Model-estimated effectiveness of single dose 9-valent HPV vaccination for HIV-positive and HIV-negative females in South Africa. Issue 32 (6th August 2018) - Tan, Nicholas; Sharma, Monisha; Winer, Rachel; Galloway, Denise; Rees, Helen; Barnabas, Ruanne V.
Abstract: Background: Women in sub-Saharan Africa have high dual burden of HPV and HIV infections, which can interact to increase cervical cancer (CC) risk. The 9-valent HPV (9vHPV) vaccine has high demonstrated effectiveness against HPV types causing 90% of CC. Additionally, one dose of the 9vHPV vaccine has the potential to achieve greater coverage at lower costs than a two-dose schedule. However, the potential impact of single-dose 9vHPV vaccine accounting for HPV-HIV interactions has not been estimated. Methods: We adapted a dynamic HIV transmission model to include HPV acquisition and CC pathogenesis and projected the impact of a single dose 9vHPV preadolescent vaccination in KwaZulu-Natal, South Africa. We report health impacts of HPV vaccination separately for HIV-positive women stratified by HIV treatment and CD4 count and HIV-negative women. Results: At 90% coverage of females age 9 years with 80% lifelong vaccine efficacy, single dose HPV vaccination was projected to reduce CC incidence by 74% and mortality by 71% in the general female population at 70 years after the start of the vaccination program. Age-standardized CC incidence and mortality reductions were comparable among HIV-negative women, HIV-positive women, and HIV-positive women on ART. Health benefits were reduced when assuming waning protection at 10, 15 and 20 years after vaccination. Discussion: Single dose 9vHPV vaccination is projected to avert substantial CC burden in South Africa and similar high HIV prevalence settings. Health benefits were comparable across all female subpopulations stratified by HIV status, CD4 count, and ART status.